Penyelesaian Perkara Pemeliharaan Anak (Alimentasi) Akibat Perceraian di Pengadilan Agama - Mardalena Hanifah (ADHAPER: Jurnal Hukum Acara Perdata, 2018)
The obligations of parents to children include the maintenance of children both their parents who are still intact in marriage or divorced. Article 156 Compilation of Islamic Law about the Result of Marriage Breakups due to Divorce which reads that a child who has not been mumayyiz has the right to obtain a hadhanah from his mother unless his mother has passed away. Children who are already mumayyiz have the right to choose to have hadhanah from their father or mother and all hadhanah costs and the livelihood of the child is borne by the father according to his ability, at least until the child is mature and can take care of their self (21 years), but in social, there are still many parents especially fathers who neglect their obligations if he has divorced his wife (mother’s children). The problem is how is the obligation of child care (alimentation) by parents due to divorce in the Religious Court and how is the legal effort if there is no obligation to carry out childcare (alimentation) by parents due to divorce in the Religious Court. The research method is normative juridical, covering research on legal principles which are something very basic in law that can be guided by the nature of descriptive research. Factors that cause obstruction of the obligation of child care (alimentation) by parents due to divorce are economic factors, legal awareness of the community, facilities in the implementation of law enforcement obligations of childcare (alimentation). The legal effort taken if the maintenance of children is not carried out is by paying money.